Étude d'un tronçon de route Laghouat - Aflou : dédoublement de la RN 23 du PK 324 au PK 329 - Daoudaoua, Abdallah; Bouras, Yacine; Bederina, Madani, Directeur de thèse; Mellal, Rachid, Directeur de thèse (My University, 2018)
This project of end of study studied a raised problem concerning the national road RN23 exactly the stretch between Laghouat -Aflou from PK 324 to PK 329 on 5 km. The problem is the insufficiency of the capacity of this road to ensure the circulation of the high traffic in the last years as well as the bad geometric shape of the road in certain regions. So, to solve this problem, we decided to make a splitting on this road, having the following characteristic: width 7 m, the shoulders of 3 m, and speed of reference Vr = 120km/h
Laghouat : Université Amar Telidji - Département de génie civil Option : Voies et ouvrages d'art